The impact of depressive symptoms on health-related quality of life in patients with subjective cognitive decline, mild cognitive impairment, and Alzheimer's disease. (31st August 2016) - Pusswald, G.; Moser, D.; Pflüger, M.; Gleiss, A.; Auff, E.; Stögmann, E.; Dal-Bianco, P.; Lehrner, J.
ABSTRACT: Background: Health-related quality of life (HRQOL) is an important issue in the context of dementia care. The purpose of this study was to investigate the association between HRQOL and depressive symptoms in patients with subjective cognitive decline (SCD) and subtypes of mild cognitive impairment (MCI) and Alzheimer´s disease (AD). Methods: In this cross-sectional, observational study, a control group and four experimental groups (SCD, non-amnestic MCI, amnesticMCI, AD) were compared. Neuropsychological measurers (NTBV) and psychological questionnaires were used for data collection. Results: The control group scored higher than patients with SCD, naMCI, aMCI, or AD for the Mental Health Component Score (MHCS) of the Short Form of the Health Survey (SF-36). The Physical Health Component Score (PHCS) of the SF-36 differed only between some groups. Furthermore, cognitive variables were more strongly associated with the physical aspects of HRQOL, whereas depressive symptoms were more strongly related with the mental aspects of HRQOL. Conclusions: HRQOL and depressive symptoms are closely related in patients with cognitive impairments. Therefore, it is of great importance to assess patients with subjective impairment carefully in terms of depressive symptoms.